Pengembangan Media Pembelajaran Monopoli pada Kelas Edukasi Laktasi untuk Meningkatkan Pengetahuan dan Sikap Ibu Hamil tentang Menyusui - Hapitria, Pepi; Nurlina, Neli (Journal of Health Science and Prevention, 2024)
Exclusive breastfeeding coverage for infants aged 0-6 months was 71.58% in 2021, but most provinces still have coverage below the national average. One of the causes is knowledge. Interesting and fun learning media can affect knowledge or learning outcomes, one of which is interactive media in the form of a monopoly game. The study aims to develop a learning media monopoly game that is feasible in terms of media and material and to determine the effectiveness of learning media monopoly games to improve the knowledge and attitudes of pregnant women in breastfeeding. This research method uses a research and development model developed by Borg and Gall consisting of 10 steps starting from potential and problems to mass production. The results showed that the feasibility aspects by material experts and users obtained an average score of 4.32 and media experts for engineering aspects 4.9 and visual communication aspects 4.62, all of which were in the good category, meaning that they were feasible and validated to be tested. The statistical test results show that there is an increase in knowledge and attitudes of pregnant women about breastfeeding after lactation education using educational media in the form of monopoly games with p-value = 0.000 < α 0.05. The conclusion is that lactation education learning media in the form of Monopoly games is effective in increasing the interest of pregnant women in breastfeeding preparation.